Highly Selective Production of Syngas from Chemical Looping Reforming of Methane with CO2 Utilization on MgO-supported Calcium Ferrite Redox Materials. (15th January 2021) - Shah, Vedant; Cheng, Zhuo; Baser, Deven S.; Fan, Jonathan A.; Fan, Liang-Shih
Graphical abstract: Highlights: Use of MgO-supported calcium ferrite redox materials for simultaneous syngas production and CO2 thermochemical splitting. >99% methane conversion with ~98% syngas selectivity and 2:1 H2 :CO ratio in a simulated co-current moving bed setup. CO2 splitting to produce CO during reduced oxygen carrier regeneration close to thermodynamic limit of ~79%. The effect of oxygen vacancy concentration of Ca2 Fe2 O5 on CH4 activation and dissociation. The lattice oxygen in corner-sharing octahedra of Ca2 Fe2 O5 acts as the efficient active sites for CO and H2 production. Abstract: Chemical looping reforming with CO2 splitting (CLRS) is an attractive process that can be used for conversion of hydrocarbons into syngas, an industrially important intermediate that serves as a building block for other value-added products. Under the chemical looping approach, the oxygen carrier that provides lattice oxygen, instead of molecular oxygen, is used for methane partial oxidation. This work focuses on MgO-supported Ca2 Fe2 O5 redox materials as the oxygen carriers for simultaneous syngas production and CO2 utilization through thermochemical CO2 splitting using a two-reactor chemical looping system. We experimentally achieve a near 100% CH4 conversion and a high syngas selectivity of >98%, which is by far the highest in chemical looping reforming systems. Complete regeneration of the reduced oxygen carriers is obtained using CO2 with ~78% conversion, thereby operating close to the thermodynamic limit. Density functional theory calculations reveal that the lattice oxygen in corner-sharing octahedra of brownmillerite structure possessed by Ca2 Fe2 O5 acts as the efficient active sites for CO and H2 production. The formed oxygen vacancy significantly reduces the energy barriers of C-H cleavage and CO formation, leading to the reactivity and selectivity enhancement. MgO assists in reactivity enhancement by enabling higher degree of Ca2 Fe2 O5 dispersion along with increasing Ca2 Fe2 O5 ′s tolerance towards sintering. These findings will contribute to the systematic design of high-performance redox materials and chemical looping processes for syngas production with CO2 utilization.